"When you were gentiles" specters of ethnicity in Roman Corinth and Paul's Corinthian correspondence - Concannon, Cavan W. 1979- (New Haven and London Yale University Press, 2014)
Cavan W. Concannon makes a significant contribution to Pauline studies by imagining the responses of the Corinthians to Paul's letters. Based on surviving written materials and archaeological research, this book offers a textured portrait of the ancient Corinthians with whom Paul conversed, argued, debated, and partnered, focusing on issues of ethnicity, civic identity, politics, and empire
pt. 1 Corinth and Corinthians between Greece and Rome -- Becoming all things: Paul and the rhetoric of ethic malleability -- Marketplaces, merchant ships, and festivals: negotiating identities in Corinth -- Speech, flattery, and the negotiation of identity for "some" Corinthians -- pt. 2 Corinth and Corinithians between past and present -- Walking in the wilderness: Israelite ancestors in the Corinthian correspondence -- "In the city of Peirene": claiming, erasing, and challenging the past in Corinth -- Usable pasts in the Corinthian wilderness: spirits, specters, and negotiations of identity at the crossroads -- Conclusing: haunted futures.
Includes bibliographical references (pages 275-296) and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Paulus; Bible -- Criticism, interpretation, etc; Bible; Ethnicity in the Bible; Gentiles in the Bible; RELIGION ; Biblical Studies ; New Testament; RELIGION ; Biblical Studies ; Paul's Letters; RELIGION ; Biblical Studies ; History & Culture; Ethnische Identität; Criticism, interpretation, etc; Korinth